Dampak Pengelolaan Sawah Secara Organik Lebih Dari Lima Tahun Terhadap C-Organik Tanah dan Ketersediaan Ammonium - Mufriah, Dini (JURNAL AGROPLASMA, 2022)
This study aims to examine the availability of soil organic C, availability of ammonium and the dynamic pattern of organic C in organically managed paddy soils for 8 to 10 years at three different lowland rice locations in Yogyakarta. The research was conducted using survey techniques and descriptive methods. The results showed that paddy fields that were given organic fertilizer for 8-10 years had higher organic C than non-organic paddy fields, namely an average of 2.10-2.70%. In organically managed paddy soils also showed a significant positive relationship between soil organic C and NH4+-dd in MS paddy soils containing clay minerals 1:1 (r= 0.71) and NK paddy soils (r= 0 .64) and PB (r= 0.77) which were dominated by clay minerals 2:1. The correlation was not significant in the non-organic managed paddy fields.Â Keywords ï¼špaddy soils, organic C,NH4+-dd